Možnosti nadomeščanja galvanskih postopkov nanašanja tankih zaščitnih prevlek z ekološko neoporečnimi PVD prevlekami - Panjan, Peter (Vakuumist, 1997)
Owing to great ecological problems the environmental ordinances in well development countries have became in the last years so strict, that the production of galvanic coatings is restricted. Therefor new ecological clean precedures, which should replaced conventional technique, are developed in recent years. On the base of our experience in the field of hard protective coatings we have suggested physical vapour deposition techniques (PVD) as an alternative procedure to conventional techniques. The problem of replacement of galvanic coatings is not only technical and ecological, but also economical. Galvanic coatings are in general cheaper than vacuum ones. However the price of galvanic coatings increase owing to the cost of cleaning of polluted water, so we can expect that the ratio between the cost of galvanic and PVD coatings will be dramatically cahnged in the near future. Thedevelopment of equipments for large scale production of PVD coatings is also progress.
Keywords: zaščitne prevleke; galvanska obdelava; ecology; ekologija; vakuumska tehnika